2013
DOI: 10.1021/ja4031648
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Dehydrogenation of Cyclohexanone to Cyclohexenone Catalyzed by Pd(DMSO)2(TFA)2: Evidence for Ligand-Controlled Chemoselectivity

Abstract: The dehydrogenation of cyclohexanones affords cyclohexenones or phenols via removal of one or two equivalents of H2, respectively. We recently reported several PdII catalyst systems that effect aerobic dehydrogenation of cyclohexanones with different product selectivities. Pd(DMSO)2(TFA)2 is unique in its high chemoselectivity for the conversion of cyclohexanones to cyclohexenones, without promoting subsequent dehydrogenation of cyclohexenones to phenols. Kinetic and mechanistic studies of these reactions reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(67 citation statements)
references
References 65 publications
1
62
1
1
Order By: Relevance
“…Pd(DMSO) 2 (TFA) 2 mediates selective dehydrogenation of cyclohexanones to cyclohexenones, 6 and mechanistic studies supported the involvement of a homogeneous catalyst. 7 Heterogeneous Pd catalysts, such as Pd/C, promote dehydrogenation of cyclohexenones to phenols under forcing conditions (e.g., 200 °C), 2a–d,3i but such catalysts are not active under the mild conditions used for the present reactions (cf. Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd(DMSO) 2 (TFA) 2 mediates selective dehydrogenation of cyclohexanones to cyclohexenones, 6 and mechanistic studies supported the involvement of a homogeneous catalyst. 7 Heterogeneous Pd catalysts, such as Pd/C, promote dehydrogenation of cyclohexenones to phenols under forcing conditions (e.g., 200 °C), 2a–d,3i but such catalysts are not active under the mild conditions used for the present reactions (cf. Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We recently investigated the mechanism of the Pd(DMSO) 2 (TFA) 2 -catalyzed oxidative dehydrogenation of cyclohexanone, 7 and the results support a catalytic cycle in which cyclohexanone undergoes reversible coordination to Pd II , followed by turnover-limiting cleavage of the α-C–H bond (Scheme 2). The resulting PdII-enolate intermediate undergoes rapid β–H elimination to afford the cyclohexenone product and a Pd II -hydride.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our results show that homogeneous and nanoparticle catalysts show different selectivity for the conversion of cyclohexanones to cyclohexenones versus phenols. 28,29 The work of Lemaire, 16,46 together with non-oxidative catalytic applications by Liu and Li, 64 demonstrates the utility of heterogeneous Pd catalysts in related applications. The development of new catalyst systems in future studies will undoubtedly play an important role in continued expansion of this field.…”
Section: Discussionmentioning
confidence: 99%
“…28 The cyclohexanone-to-cyclohexenone step exhibited only minor rate dependence on DMSO (Scheme 16A); however, high product yield was obtained only in the presence of DMSO. Rapid formation of Pd black and catalyst deactivation occurred in the absence of DMSO.…”
Section: Partial Dehydrogenation Of Cyclohexanones and Acyclic Ketmentioning
confidence: 99%
“…[12,13] In a series of elegant studies the authors demonstrated Pd II salts coupled with O 2 as the oxidant (acceptor) to be an effective system for the aerobic dehydrogenation of cyclic ketones to generate α,β unsaturated ketones and phenols. [14]…”
Section: Introductionmentioning
confidence: 99%